PKM. KEGIATAN PENGABDIAN MASYARAKAT PELATIHAN KEMAMPUAN VOCABULARY BAHASA INGGRIS MELALUI DEMOSTRASI PENGENALAN MAKANAN 4 SEHAT 5 SEMPURNA - Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi; Ni Putu Lindawati (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
The ability to apply English through demonstrations eating 4 healthy 5 perfect food is the ability to know all the words about fruit and vegetables, or vocabulary, or diction that refers to healthy 5 perfect concepts, to express ideas in speaking and in writing English. The purpose of this social activity are: (1) imitate pronouncing English words according to the pictures, (2) Mention English words according to the pictures, (3) match the sounds of English words with the pictures that symbolize them, and (4) link the pictures and the written language words English. The method used is socialization and mentoring. Presentation of material on improving English skills by learning vocabulary through demonstration methods of eating behavior 4 healthy 5 perfect. The participants in this activity were 16 Neo Genesis Kindergarten students. The results of this social activity are: (1) carrying out an approach method through field observations, (2) the team provides facilities in the form of delivering materials, prizes, and providing consumption in the form of healthy food such as fresh fruit to students at Neo Genesis Kindergarten, Dalung, district North Kuta, Badung regency. (3) training through materials, games and question and answer sessions, (4) evaluation of activities regarding the understanding of extension participants. From the results obtained, it can create PKM activities that are useful in relation to improving English skills by learning vocabulary through demonstration methods of eating behavior 4 healthy 5 perfect.